Incidence, Characteristics, and Outcomes of Clinically Undetected Bacteremia in Children Discharged Home From the Emergency Department. Issue 10 (14th July 2022) - Golan, Naama; Mor, Meirav; Yaniv, Noga; Berant, Ron; Bressan, Silvia; Altberg, Gal; Samuel, Nir
Abstract : Background: Despite a recent decline in the rates of invasive infections, bacteremia in young children remains a significant challenge. We aimed to describe patient characteristics, microbial etiology, and outcomes of bacteremic, well-appearing children 3–36 months of age who were discharged home from the pediatric emergency department (PED) on their index visit. Methods: A retrospective cohort study in the PED of a tertiary children's hospital from 1 June 2015 until 30 June 2021. We included all well appearing, immunocompetent infants 3–36 months old evaluated for fever and discharged home from the PED after a blood culture was drawn. We extracted demographic, clinical and laboratory data from the patient's electronic medical records for the index visit and subsequent encounters. Results: During the study period, 17, 114 children evaluated for fever met the inclusion criteria. Seventy-two patients (0.42%) had positive cultures for known pathogens. Thirty-six (50%) were male and 36 (50%) younger than 1 year. The most common isolates were S. pneumonia 26%. (n = 19), K. Kingae 25%. (n = 18) and Salmonella spp. 13.9% (n = 10). Sixty patients (85.7%) were recalled to the ED or had a scheduled appointment, 10 (14.3%) returned spontaneously and two were followed up by phone. The median time between visits was 28.7 hours (IQR 19.1–41.1). One patient was admitted to intensive care during the course of hospitalization. There were no deaths. Conclusion: The rate of undetected true bacteremia in our study was low and our data suggest that significant clinical deterioration during the first 24 hours is rare.